Volatilitas Nilai Tukar dan Harga Komoditas Global selama Krisis Laut Merah - Agustina, Agustina; Barus, Andreani Caroline; Firza, Syafira Ulya; Halim, Fandi; Br Ginting, Litka Tiadoraria (Penerbit Goodwood, 2024)
Purpose: This study aims to determine the most suitable model for assessing the volatility of currency exchange rates for Indonesia, Malaysia, and Singapore, as well as global commodity prices, specifically gold and crude oil. Methodology: The research was conducted by performing various tests using the SPSS version 25 application, followed by a volatility analysis employing the GARCH method with the E-Views version 9 application. Results: The study reveals that the Red Sea crisis significantly impacts global investment volatility. The EGARCH(1,1) model best describes the volatility of USD/IDR, USD/SGD, and crude oil prices, while the GJR-GARCH(1,1) model is most suitable for USD/MYR, and the GARCH(1,1) model fits gold price volatility. Limitations: This study is limited by its focus on only three countries (Indonesia, Malaysia, and Singapore) and two commodities (gold and crude oil). Additionally, the analysis only covers the period following the first attack in the Red Sea crisis. Contribution: This research provides valuable insights for decision-makers and investors by highlighting the impact of global events on market volatility.